The Impact of Psychopathology Associated With Childhood Trauma on Quality of Life in Portuguese Adolescents: A Two-Wave Longitudinal Study - Pinto, Ricardo; De Castro, Maria Vieira; Silva, Laura; Jongenelen, Inês; Maia, Angela; Levendosky, Alytia A. (Frontiers in Psychiatry, 2021)
Introduction. The aim of this study was to explore the mediating effect of psychopathology between childhood adversity and trauma and quality of life (QOL) in adolescents. The second aim of the study was testing the moderation by social support of this mediation effect. Method. Self-reports of childhood adversity and trauma, QOL, social support, and psychopathology were collected from 150 Portuguese adolescents’ exposure to at least one traumatic event or one childhood adversity (Mage= 16.89, SD = 1.32). The surveys were administered in two moments, with an approximate time interval of one year. Results. Indirect effects were observed for depression (B = -0.33, CI[-0.62, -0.11]), somatization (B = -0.52, CI[-0.82, -0.23]), and post-traumatic stress symptoms (PTSS) (B = -0.23, CI[-0.45, -0.01]), but not for anxiety (B = 0.20, CI[-0.08, 0.50]). A moderated mediation was found between social support and depression (B = -.10, CI[−16, -.04]), and PTSS (B = .03, CI[-0.1, -.05]), but not for somatization (B = -.02, CI[-0.8, .05]). Conclusions. We found that depression and somatization had a large effect size, and PTSS a medium effect size, as mediators between adversity/trauma and QOL. Anxiety did not mediate this relationship. The moderated-mediation effect of social support was only found for depression and PTSS. The improvement of QOL in adolescents exposed to childhood adversity and trauma should include the assessment of psychopathology symptoms and social support, with the aim of identifying risk and protective factors.